Malaysia pasca rasisme : wajah baru politik Malaysia II - Mujahid Yusof Rawa; Abdul Muqit Muhammad (Petaling Jaya, Selangor : Ilham Books, 2014)
On racism and political culture in Malaysia.
In Malay.
Keywords: Political culture -- Malaysia; Malaysia -- Politics and government